ANALISIS TEKNIKAL GUNA MENENTUKAN SINYAL JUAL DAN SINYAL BELI DALAM TRADING SAHAM (STUDI : PERUSAHAAN SUB SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2017) - Juliyana , Nanda; Fauji, Diah Ayu Septi (Universitas Nusantara PGRI Kediri, 2018)
In carrying out stock investments in capital markets needed expertise in reading stock market information. Reading stock market information can use a chart of stock price movements. But so far not many college students who can read stock market information by using technical analysis. This is evident from the author’s initial survey to forty college students of the University of Nusantara PGRI Kediri four level management program only four college students who know about technical analysis and none of them know about the MACD indicator. The purpose of this research is to find out when there is a sell signal and buy signal using the MACD indicator and determine the trend that occurs in the stock price movement of the property and real estate sub-sector companies during the 2015-2017 period, to determine investment decisions which must be done based on the trends that occur with a sell signal or buy signal that is formed and to determine the accuracy of the sell signal or buy signal that is formed from the MACD indicator. The approach used is quantitative approach with descriptive analysis. Data analysis technique used is technical analysis with MACD indicator. The research conclusions are (1) BIKA produces one buy signal, DMAS produces six sell signal and five buy signal, MMLP produces four buy signal, PPRO produces one sell signal and one buy signal, TARA produces seven sell signal. (2) BIKA experiencing downtrend and sideways trend, DMAS experiencing sideways trend, uptrend, and downtrend, MMLP experiencing downtrend, uptrend, and sideways trend, PPRO experiencing uptrend, sideways trend, and downtrend, TARA experiencing uptrend and sideways trend. (3) Good investments decisions to do are to purchase DMAS and MMLP shares and sell DMAS, PPRO, and TARA shares. (4) Based on the results of the paired sample t-test, there is no significant difference between the sell signal and the buy signal before MACD with the sell signal and buy signal after MACD so that the technical analysis with MACD indicator is accurate and can be used as a guidelines in determining the sell signal and buy signal in stock trading in property and real estate sub-sector companies listed on the Indonesia Stock Exchange.